Le débat sur l’architecture rurale en Italie et l’exposition de Giuseppe Pagano à la Triennale de 1936 - Giovanna D’Amia (In Situ, 2013)
In Italy, in the 30s, rural architecture was the principal subject of a debate between ethnologists, geographers, architects and town planners. The fascist politics of the agrarian reorganization aroused interest in this topic, but the intellectual reflection was also stimulated by the research of an Italian modern architecture approach to the problem. In this context Giuseppe Pagano organized the 6th Triennale’s exposition in order to show the aesthetic value of the functionality and to investigate the relationship of cause and effect that determine the architectural form.